A sodium ion battery layered oxide positive electrode material and preparation method thereof
By doping titanium source into the layered oxide positive electrode material of sodium ion battery and adopting ball milling and calcining steps, the residual alkali value of the material is successfully reduced, solving the problem of unstable material performance in the prior art, and achieving the effect of high cycle stability and rate performance.
Patent Information
- Application Number
- CN202410172425.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-06
- Publication Date
- 2025-04-04
AI Technical Summary
The residual alkali value of the existing sodium ion battery layered oxide positive electrode materials is high, resulting in changes in the material structure and unstable battery performance, and lack of effective methods to reduce residual alkali.
By doping a titanium source, combined with a ball milling and calcining step, a sodium ion battery layered oxide positive electrode material with reduced residual alkali value was prepared.
It achieves the reduction of the residual alkali value of the material, while maintaining high cycle stability and rate performance, and is suitable for the application of sodium ion batteries.
Smart Images

Figure CN119764356A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion batteries, in particular to a sodium ion battery layered oxide positive electrode material and a preparation method thereof. Background Art
[0002] In the current field of sodium batteries, sodium ion cathode materials (especially layered transition metal oxides) have serious residual alkali on the surface. There is currently no mature method to reduce the alkalinity of the materials. These residual alkalis will react with H in the air. 2 O and CO 2 The presence of residual alkali will also affect the performance of the battery cell, including making the battery cell more prone to gas production (such as CO 2 , CO, H 2 In addition, the residual alkali makes the interface impedance of the sodium ion positive electrode material larger, resulting in a decrease in the electrochemical performance of the battery. Therefore, it is necessary to reduce the residual alkali content of the sodium ion positive electrode material.
[0003] Patent application CN116154341A discloses a method for reducing the residual alkali content of a sodium ion battery layered oxide positive electrode material, which specifically comprises the following steps: (1) dispersing the sodium ion battery layered oxide positive electrode material in anhydrous glycerol or a mixture of anhydrous glycerol and anhydrous alcohol; (2) stirring to completely dissolve the residual alkali, and filtering; (3) washing the filtered positive electrode material with anhydrous alcohol, and vacuum drying to obtain a layered oxide positive electrode material with reduced residual alkali content. This method requires the use of a solvent to dissolve the material, but some layered oxides undergo structural changes after contact with the solvent, which results in unstable battery performance before and after treatment. Therefore, the applicability of the above method is relatively limited. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of existing layered oxides in reducing residual alkali, provide a sodium ion battery layered oxide positive electrode material and a preparation method thereof, adopt a doping method to reduce the residual alkali value of the material, and maintain a high cycle stability and rate performance.
[0005] The specific plan is as follows:
[0006] A method for preparing a sodium ion battery layered oxide positive electrode material comprises the following steps:
[0007] S1, mixing at least one of a sodium source and a titanium source and a composite oxide of nickel, iron and manganese or a hydroxide of nickel, iron and manganese;
[0008] S2, ball milling to obtain a mixed material;
[0009] S3. Calcinate the mixture in an oxygen-containing atmosphere to obtain a layered oxide cathode material for a sodium-ion battery.
[0010] Further, the sodium source is at least one of sodium carbonate, sodium bicarbonate, and sodium oxide; the titanium source is at least one of titanium tetrachloride, titanium trichloride, titanium dioxide, titanium carbonate, and titanium hydroxide; the molar ratio of nickel, iron, and manganese in the nickel-iron-manganese composite oxide is 0-1:0-1:0-1, preferably Ni 0.33 Fe 0.33 Mn 0.33 O; the molar ratio of nickel, iron, and manganese in the nickel-iron-manganese hydroxide is 0-1:0-1:0-1, preferably Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 .
[0011] Further, the raw materials are mixed according to the target chemical formula Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 , where 0 < x < 3%, preferably, 1% ≤ x ≤ 2%, more preferably, x = 1.5%.
[0012] Further, the ball milling is carried out by dry ball milling for 2-12 h;
[0013] Optionally, the calcination temperature is 800-900 °C and the time is 6-12 h.
[0014] Further, the method for preparing the layered oxide cathode material for a sodium-ion battery includes the following steps:
[0015] S1. Mix the titanium source and the nickel-iron-manganese composite oxide or nickel-iron-manganese hydroxide;
[0016] S2. Carry out ball milling to obtain a primary mixture;
[0017] S3. Calcinate the primary mixture in an oxygen-containing atmosphere at 500-600 °C for 6-12 h to obtain a precursor of the cathode material for a sodium-ion battery;
[0018] S4. Mix the precursor of the cathode material for a sodium-ion battery with the sodium source;
[0019] S5. Carry out ball milling to obtain a secondary mixture;
[0020] S6. Calcinate the secondary mixture in an oxygen-containing atmosphere at 800-900 °C for 6-12 h to obtain the layered oxide cathode material for a sodium-ion battery.
[0021] Furthermore, the preparation method of the sodium ion battery layered oxide positive electrode material comprises the following steps: S1, mixing the sodium source, the titanium source, and the composite oxide of nickel, iron and manganese or the hydroxide of nickel, iron and manganese; S2, ball milling to obtain a mixture; S3, calcining the mixture at 800-900° C. for 6-12 hours in an oxygen-containing atmosphere to obtain the sodium ion battery layered oxide positive electrode material.
[0022] The present invention also protects the sodium ion battery layered oxide positive electrode material prepared by the method for preparing the sodium ion battery layered oxide positive electrode material, which has at least one of the following (1) to (5):
[0023] (1) The sodium ion battery layered oxide positive electrode material is in the form of spherical particles with a size of 10-30 microns, uniform size distribution, and clear surface texture;
[0024] (2) The surface residual alkali value of the sodium ion battery layered oxide positive electrode material is pH = 11-12.5;
[0025] (3) The initial discharge capacity of the sodium ion battery layered oxide positive electrode material at 0.1C is 127-134 mAh g -1 ;
[0026] (4) The sodium ion battery layered oxide positive electrode material has a capacity retention rate of 97.0-98.5% after 120 cycles at a voltage window of 2-4 V and a rate of 0.1C;
[0027] (5) The capacity retention rate of the sodium ion battery layered oxide positive electrode material after 20 cycles at 0.5C, 1C, 3C, and 5C is independently 97.56-99.89%.
[0028] The present invention also protects a positive electrode, comprising the sodium ion battery layered oxide positive electrode material.
[0029] The present invention also protects a sodium ion battery comprising the positive electrode.
[0030] Beneficial effects: The method for preparing the layered oxide positive electrode material for sodium ion batteries of the present invention can reduce the residual alkali in the material by adding a titanium source for doping modification, and the material can maintain its electrochemical properties, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings will be briefly introduced below. Obviously, the accompanying drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.
[0032] Figure 1This is a SEM image of a material provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0033] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. In the examples, those without specifying specific techniques or conditions are carried out according to the techniques or conditions described in the literature in this area or according to the product specification. Those without specifying the manufacturer of reagents or instruments used are all conventional products that can be obtained commercially. In the following examples, if not clearly stated, "%" refers to weight percentage.
[0034] Example 1
[0035] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0036] S1, with Na 2 CO 3 、Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 , titanium dioxide as raw materials, and the raw material dosage is based on the target chemical formula of Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 , where x = 0%;
[0037] S2, dry ball milling in a pot mill for 4 h to obtain a mixed material;
[0038] S3, calcining the mixture at 860° C. for 12 hours in an oxygen-containing atmosphere to obtain the sodium ion battery positive electrode material.
[0039] Example 2
[0040] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0041] S1, with Na 2 CO 3 、Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 , titanium dioxide as raw materials, and the raw material dosage is based on the target chemical formula of Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2, where x = 0.5%,
[0042] S2, dry ball milling in a pot mill for 4 h to obtain a mixed material;
[0043] S3, calcining the mixture at 860° C. for 12 hours in an oxygen-containing atmosphere to obtain the sodium ion battery positive electrode material.
[0044] Example 3
[0045] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0046] S1, with Na 2 CO 3 、Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 , titanium dioxide as raw materials, and the raw material dosage is based on the target chemical formula of Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 , where x = 1%,
[0047] S2, dry ball milling in a pot mill for 4 h to obtain a mixed material;
[0048] S3, calcining the mixture at 860° C. for 12 hours in an oxygen-containing atmosphere to obtain the sodium ion battery positive electrode material.
[0049] Example 4
[0050] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0051] S1, with Na 2 CO 3 、Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 , titanium dioxide as raw materials, and the raw material dosage is based on the target chemical formula of Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 , where x = 1.5%,
[0052] S2, dry ball milling in a pot mill for 4 h to obtain a mixed material;
[0053] S3, calcining the mixture at 860° C. for 12 hours in an oxygen-containing atmosphere to obtain the sodium ion battery positive electrode material.
[0054] Example 5
[0055] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0056] S1, with Na 2 CO 3 、Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 , titanium dioxide as raw materials, and the raw material dosage is based on the target chemical formula of Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 , where x = 2%,
[0057] S2, dry ball milling in a pot mill for 4 h to obtain a mixed material;
[0058] S3, calcining the mixture at 860° C. for 12 hours in an oxygen-containing atmosphere to obtain the sodium ion battery positive electrode material.
[0059] Example 6
[0060] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0061] S1, with Na 2 CO 3 、Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 , titanium dioxide as raw materials, and the raw material dosage is based on the target chemical formula of Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 , where x = 2%,
[0062] S2, dry ball milling in a pot mill for 4 h to obtain a mixed material;
[0063] S3, calcining the mixture at 860° C. for 12 h in an oxygen-containing atmosphere to obtain a primary calcined product;
[0064] S4, calcining the primary calcination product at 960° C. for 8 h to obtain the sodium ion battery positive electrode material.
[0065] Example 7
[0066] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0067] S1, Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 , titanium dioxide as raw materials, and the raw material dosage is based on the target chemical formula of Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 The molar ratio of titanium, nickel, iron and manganese is determined.
[0068] S2, dry ball milling in a pot mill for 4 h to obtain a primary mixture;
[0069] S3, calcining the primary mixture at 500° C. for 12 h in an oxygen-containing atmosphere to obtain a sodium ion battery positive electrode material precursor;
[0070] S4, mixing the sodium ion battery positive electrode material precursor with Na 2 CO 3 Mixing, the raw material dosage is based on the target chemical formula Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 The molar ratio of titanium and sodium is determined as follows: x = 2%,
[0071] S5, dry ball milling in a pot mill for 4 h to obtain a secondary mixture;
[0072] S6, calcining the secondary mixture at 860° C. for 12 hours in an oxygen-containing atmosphere to obtain the sodium ion battery positive electrode material.
[0073] Example 8
[0074] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0075] S1, Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 、Na 2 CO 3 The raw materials are mixed, and the raw material dosage is based on the target chemical formula Ti x Na 1-x Ni 0.33 Fe0.33 Mn 0.33 O 2 The molar ratio of sodium, nickel, iron and manganese is determined, where x = 2%,
[0076] S2, dry ball milling in a pot mill for 4 h to obtain a primary mixture;
[0077] S3, calcining the primary mixed material at 500° C. for 12 h in an oxygen-containing atmosphere to obtain a primary positive electrode material;
[0078] S4, the primary positive electrode material is mixed with titanium oxide, and the raw material dosage is based on the target chemical formula Ti x Na 1- x Ni 0.33 Fe 0.33 Mn 0.33 O 2 The molar ratio of titanium and sodium is determined as follows: x = 2%,
[0079] S5, dry ball milling in a pot mill for 4 h to obtain a secondary mixture;
[0080] S6, calcining the secondary mixture at 860° C. for 12 hours in an oxygen-containing atmosphere to obtain the sodium ion battery positive electrode material.
[0081] Example 9
[0082] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0083] S1, with Na 2 CO 3 、Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 , titanium hydroxide as raw materials, and the raw material dosage is based on the target chemical formula of Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 , where x = 1%,
[0084] S2, dry ball milling in a pot mill for 4 h to obtain a mixed material;
[0085] S3, calcining the mixture at 820° C. for 12 hours in an oxygen-containing atmosphere to obtain the sodium ion battery positive electrode material.
[0086] Example 10
[0087] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0088] S1, sodium oxide, Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 , titanium carbonate as raw materials, and the raw material dosage is based on the target chemical formula of Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 , where x = 1.5%,
[0089] S2, dry ball milling in a pot mill for 4 h to obtain a mixed material;
[0090] S3, calcining the mixture at 880° C. for 12 hours in an oxygen-containing atmosphere to obtain the sodium ion battery positive electrode material.
[0091] Comparative Example 1
[0092] Referring to Example 4, the difference is that titanium dioxide is replaced by aluminum oxide, that is, aluminum metal is used for doping, and the specific steps are as follows:
[0093] S1, with Na 2 CO 3 、Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 、Al 2 O 3 The raw materials are mixed, and the raw material dosage is based on the target chemical formula of Al x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 , where x = 1.5%,
[0094] S2, dry ball milling in a pot mill for 4 h to obtain a mixed material;
[0095] S3, calcining the mixture at 860° C. for 12 h in an oxygen-containing atmosphere to obtain a comparative positive electrode material.
[0096] Comparative Example 2
[0097] Referring to Example 4, the difference is that magnesium fluoride is used to replace titanium dioxide, that is, magnesium metal is used for doping, and the specific steps are as follows:
[0098] S1, with Na 2 CO 3 、Ni 0.33 Fe 0.33Mn 0.33 (OH) 2 MgF 2 The raw materials are mixed, and the raw material dosage is based on the target chemical formula of Mg x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 , where x = 1.5%,
[0099] S2, dry ball milling in a pot mill for 4 h to obtain a mixed material;
[0100] S3, calcining the mixture at 860° C. for 12 h in an oxygen-containing atmosphere to obtain a comparative positive electrode material.
[0101] Comparative Example 3
[0102] Referring to Example 4, the difference is that zinc oxide is used to replace titanium dioxide, that is, zinc metal is used for doping, and the specific steps are as follows:
[0103] S1, with Na 2 CO 3 、Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 , ZnO as raw materials, and the raw material dosage is based on the target chemical formula of Zn x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O 2 , where x = 1.5%,
[0104] S2, dry ball milling in a pot mill for 4 h to obtain a mixed material;
[0105] S3, calcining the mixture at 860° C. for 12 h in an oxygen-containing atmosphere to obtain a comparative positive electrode material.
[0106] Performance Testing
[0107] (1) The sodium ion battery positive electrode material prepared in Example 4 was analyzed for morphology. Figure 1 As shown, it can be seen that the particles are spherical, about 10-30 microns, evenly distributed in size, with clear surface texture, and are composed of multiple elements such as nickel, iron, manganese, sodium, and titanium.
[0108] (2) 10 g of the prepared sodium ion battery positive electrode material was dispersed in 100 mL of deionized water, sealed with plastic wrap, and magnetically stirred at 300 rpm for 5 minutes. The clear liquid was filtered and the pH value was tested. The results are shown in Table 1.
[0109] Table 1 Alkaline test results
[0110]
[0111] It can be seen from Table 1 that the sodium ion battery positive electrode material prepared by the present invention has a lower residual alkalinity value than the undoped Example 1, and its pH is 11-12.5. At the same time, titanium doping can significantly reduce the residual alkalinity value of the material, while other metals such as aluminum, magnesium, and zinc have little significant reduction effect.
[0112] Among them, Example 4 is doped with 1.5% titanium, and the residual alkali value of the material after calcination is the lowest. Example 7 first performs titanium doping and then sodium doping, which helps to further reduce the residual alkali value. Example 8 first performs sodium doping and then titanium doping, and the effect of reducing alkalinity is relatively weakened.
[0113] (3) At room temperature, the positive electrode material prepared as above was used as the active material, and the slurry was prepared according to the mass ratio of active material: binder: conductive agent = 8:1:1, wherein the binder was polyvinyl alcohol and the conductive agent was graphite. After baking, the electrode sheet was obtained, and then metallic sodium was used as the counter electrode, and the sodium ion battery electrolyte (polyfluoride sodium ion battery electrolyte) was used as the electrolyte, and the button battery was assembled under a vacuum environment. The electrochemical properties of the button battery were tested, including constant current charge and discharge (GCD), cycle stability and rate performance. Among them, the main conditions of constant current charge and discharge (GCD) include 0.1C charge and discharge at room temperature; the main conditions of cycle stability include charge and discharge at a voltage window of 2-4V and a rate of 0.1C at room temperature (the capacity retention rate is less than 80% to complete the test); the main conditions of rate performance include 20 cycles of charge and discharge at 0.1C, 0.5C, 1C, 3C, and 5C at room temperature. The test results are shown in Table 2.
[0114] Table 2 Battery performance test results
[0115]
[0116] It can be seen from Table 2 that the electrochemical performance of the sodium ion battery positive electrode material prepared by the present invention is not much changed after adding titanium and calcining, and the initial discharge specific capacity is 127-134 mAh·g -1 , the capacity is relatively high. At the 2-4V voltage window and 0.1C rate, after 120 cycles, the capacity retention rate is 97.0-98.5%. The capacity retention rates after 20 cycles at 0.5C, 1C, 3C, and 5C are each independently 97.56-99.89%, which has good cycle performance.
[0117] Among them, Example 4 is doped with 1.5% titanium, and its electrochemical performance further improves the battery's gram capacity, rate performance and cycle life. Example 6 was calcined twice, which can further improve the battery's gram capacity and rate performance, but the cycle life is reduced. Example 7 first performs titanium doping and then sodium doping, which can further improve the battery's gram capacity, rate performance and cycle life. Example 8 first performs sodium doping and then titanium doping, which further improves the battery's gram capacity and rate performance, but the cycle life is correspondingly reduced.
[0118] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0119] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0120] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a layered oxide positive electrode material for a sodium ion battery, characterized in that: The following steps are involved: S1, mixing at least one of a sodium source and a titanium source and a composite oxide of nickel, iron and manganese or a hydroxide of nickel, iron and manganese; S2, ball milling to obtain a mixed material; S3, calcining the mixture in an oxygen-containing atmosphere to obtain a layered oxide positive electrode material for a sodium ion battery.
2. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: The sodium source is at least one of sodium carbonate, sodium bicarbonate, and sodium oxide; the titanium source is at least one of titanium tetrachloride, titanium trichloride, titanium dioxide, titanium carbonate, and titanium hydroxide; the molar ratio of nickel, iron, and manganese in the nickel-iron-manganese composite oxide is 0-1:0-1:0-1, preferably Ni 0.33 Fe 0.33 Mn 0.33 O; the molar ratio of nickel, iron and manganese in the nickel, iron and manganese hydroxide is 0-1:0-1:0-1, preferably Ni 0.33 Fe 0.33 Mn 0.33 (OH)2.
3. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 2, characterized in that: The raw material mixture has a target chemical formula of Ti x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O2, where 0 < x < 3%, preferably, 1% ≤ x ≤ 2%, more preferably, x = 1.5%.
4. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: The ball milling is dry ball milling, and the time is 2-12 hours.
5. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: The calcination temperature is 800-900° C. and the calcination time is 6-12 hours.
6. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing the titanium source and the composite oxide of nickel, iron and manganese or the hydroxide of nickel, iron and manganese; S2, ball milling to obtain a primary mixture; S3, calcining the primary mixture at 500-600°C for 6-12h in an oxygen-containing atmosphere to obtain a sodium ion battery positive electrode material precursor; S4, mixing the sodium ion battery positive electrode material precursor with the sodium source; S5, ball milling to obtain a secondary mixture; S6, calcining the secondary mixture at 800-900°C for 6-12h in an oxygen-containing atmosphere to obtain the sodium ion battery layered oxide positive electrode material.
7. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing the sodium source, the titanium source, and the composite oxide of nickel, iron and manganese or the hydroxide of nickel, iron and manganese; S2, ball milling to obtain a mixture; S3, calcining the mixture at 800-900° C. for 6-12 hours in an oxygen-containing atmosphere to obtain the layered oxide positive electrode material for a sodium ion battery.
8. The sodium ion battery layered oxide positive electrode material prepared by the method for preparing the sodium ion battery layered oxide positive electrode material according to any one of claims 1 to 7 is characterized in that: Having at least one of the following (1) to (5): (1) The sodium ion battery layered oxide positive electrode material is in the form of spherical particles with a size of 10-30 microns, uniform size distribution, and clear surface texture; (2) The surface residual alkali value of the sodium ion battery layered oxide positive electrode material is pH = 11-12.5; (3) The initial discharge capacity of the sodium ion battery layered oxide positive electrode material at 0.1C is 127-134 mAh g -1 ; (4) The sodium ion battery layered oxide positive electrode material has a capacity retention rate of 97.0-98.5% after 120 cycles at a voltage window of 2-4 V and a rate of 0.1C; (5) The capacity retention rate of the sodium ion battery layered oxide positive electrode material after 20 cycles at 0.5C, 1C, 3C, and 5C is independently 97.56-99.89%.
9. A positive electrode comprising the sodium ion battery layered oxide positive electrode material according to claim 8.
10. A sodium ion battery comprising the positive electrode according to claim 9.
Citation Information
Patent Citations
Method for reducing residual alkali amount of layered oxide positive electrode material of sodium-ion battery
CN116154341A